Renewal of Islamic Inheritance Law in Indonesia: An Examination of Wasatiyyah Theory - Alwi, Alwi Haidar (Indonesian Association of Islamic Family Law Lecturers, 2023)
Problem statement: The reform of Islamic inheritance law in Indonesia is an urgent necessity, given the challenges of the modern era that demand laws that are more adaptive and contextual. The primary issues encountered include the incompatibility between classical Islamic inheritance law and the needs of contemporary society, particularly concerning gender equality, flexibility in the distribution of inheritance, and the recognition of the principle of mutual agreement among heirs. Objective: This study aims to explore the wasatiyyah theory as a foundation for the reform of Islamic inheritance law, with the objective of achieving a balance between Sharia values, social conditions, and the principle of public interest. Methods: The study employs a qualitative methodology with a legal-normative approach. Data sources were obtained through the analysis of legal documents and literature pertinent to this research. This study also utilises descriptive and argumentative analysis to connect the theory of wasatiyyah with the concept of inheritance law reform. Results: This study indicate that the theory of wasatiyyah can provide a robust foundation for reforming Islamic inheritance law in Indonesia. This theory emphasises balance between Sharia texts and social context, thereby facilitating agreement among heirs and promoting more equitable flexibility in inheritance distribution. The novelty of this research lies in the formulation of an integrative approach that is not only oriented towards Sharia norms but also considers aspects of social justice and public interest. Conclusion: This research contributes to providing a new perspective in the study of Islamic law, particularly inheritance law, that is more relevant to the needs of contemporary society.